The embrace of nothing : shifting representations of the absurd from Samuel Beckett to Sofia Coppola. - Nurul Izzati Liyana Abdul Haris (2013)
The essay looks at the shifting presentation of the Absurd through the works of playwright Samuel Beckett and film director Sofia Coppola, specifically looking at Beckett’s Waiting For Godot, Endgame and Krapp’s Last Tape, and Coppola’s Marie Antoinette, Lost In Translation and Somewhere. Absurdist philosophy studies the conflict between the human tendency to seek inherent value and meaning in life and the inability to find any. Yet, some Absurdists maintain that one should embrace the absurd nature of the human condition while still continuing to explore and seek meaning. Indeed we see in Coppola’s films elements of the Absurd, albeit less explicit in the way it is portrayed in Beckett's Absurdist dramas. A comparison of the two artists is thus necessary to yield a comprehensive study of Coppola’s cinematographic decisions, which then serves to elucidate the ways that the Absurd is portrayed in their works. A proper understanding of the Absurd would shed light on the ways in which the audience could embrace the absurdity of human life, even while still being motivated to seek innate meaning in the universe.